1986
DOI: 10.1021/jm00155a011
|View full text |Cite
|
Sign up to set email alerts
|

Drug design via pharmacophore identification. Dopaminergic activity of 3H-benz[e]indol-8-amines and their mode of interaction with the dopamine receptor

Abstract: The design and synthesis of a series of 3H-benz[e]indol-8-amines are described. Two of the compounds are potent, orally active dopaminergic agents as established by their ability to induce contralateral turning in rats with unilateral 6-hydroxydopamine-induced lesions of the nigrostriatal pathway, to induce ambulation in rats rendered akinetic by bilateral injections of 6-hydroxydopamine into the anterolateral hypothalamus, and to antagonize reserpine-induced catalepsy in mice. The dopamine agonist activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…Benz[ e ]indole ( 67 , Figure ), the pyrrolo analogue of the dopaminergic agonist ( 69 ), displays potent dopaminergic properties, is orally active and has a longer duration of action than 69 . The effectiveness of the pyrrolo ring of 67 as a bioisosteric replacement for the phenolic hydroxyl group has been ascribed to the ability of both groups to hydrogen bond to a common acceptor nucleus on the dopamine receptor . Evidence for the involvement of the hydrogen bond formation being related to the success of this bioisosteric replacement was provided by the lack of activity observed with the N -methylpyrrolo analogue 68 .…”
Section: Hydroxyl Group Bioisosteresmentioning
confidence: 99%
“…Benz[ e ]indole ( 67 , Figure ), the pyrrolo analogue of the dopaminergic agonist ( 69 ), displays potent dopaminergic properties, is orally active and has a longer duration of action than 69 . The effectiveness of the pyrrolo ring of 67 as a bioisosteric replacement for the phenolic hydroxyl group has been ascribed to the ability of both groups to hydrogen bond to a common acceptor nucleus on the dopamine receptor . Evidence for the involvement of the hydrogen bond formation being related to the success of this bioisosteric replacement was provided by the lack of activity observed with the N -methylpyrrolo analogue 68 .…”
Section: Hydroxyl Group Bioisosteresmentioning
confidence: 99%
“…6 This gave an indication of the direction of a possible H-bond of 7-OH-DPAT (lb) in the dopamine site of the Da receptor even though the possibility that compound 3 is poorly active by steric interference cannot be outruled. Later Wikstróm et al 7 showed that compound 2b, the dimethyl analog of 2a, possesses considerable 5-HTia agonist properties in addition to its dopaminergic activity, reported by Asselin et al 1 It was speculated that the high electron density in the indole 3-position (corresponding to 1-position of 2b), resembled the 8-oxygen in 8-hydroxy-2-(Ñ,2V-dipropylamino)-l,2,3,4-tetrahydronaphthalene (8-OH-DPAT, la), the well-studied standard serotonin 5-HTia agonist.8-15 If one considers hydrogen bond attraction to the receptor protein, it is possible that in the case of 2b the partial negative charge of the -electron cloud nearby Cl serves as a hydrogen bond acceptor, since the hydrogen at Cl presumably is poor as a donor. 16 However, the relatively low binding (compared to 8-OH-DPAT) of the dimethyl compound 2b indicated that a better probe for this hypothesis would be compound 2a.…”
Section: Introductionmentioning
confidence: 94%
“…This approach has been useful for determining the nature of the hydrogen bonding between phenol-containing ligands and receptor proteins. [1][2][3][4] For example Asselin et al1 demonstrated that the "indolic" aminotetralin 2a (Figure 1) showed dopaminergic effects and thus mimicked the action of 7-hydroxy-2-(iV^V-dipropylamino)-l,2,3,4-tetrahydronaphthalene (7-OH-DPAT, lb). It was pointed out that, since the lone pairs in the indole nitrogen of 2a cannot participate in a H-bond (due to its contribution to the aromaticity), the indole NH moiety can only participate as a H-bond donor (electron-pair acceptor).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 3–5 are examples of heterocyclic isosteres of hydroxy‐2‐aminotetralins, which were shown to possess DA agonist activity (Fig. ) . This encouraged us to replace the phenolic portion of 2‐aminotetralin with ester and pyridine‐substituted pyridazines and pyrroles may be the compounds with potential dopaminergic activities.…”
Section: Introductionmentioning
confidence: 99%